2019
DOI: 10.3390/su11061632
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of City Sustainability Using MCDM with Interdependent Criteria Weight

Abstract: The Capital Economic Circle is an important planning project in China. Sustainability is a key factor for the long-term development of the Capital Economic Circle. In this paper, we investigated the sustainability of 13 cities in the Capital Economic Circle using three dimensions: economy, society, and environment. The induced ordered weighted averaging (IOWA) operator was used for the aggregation of criteria data. The order-inducing variable in the IOWA operator was measure by the correlation degree of a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…They concluded that considering sustainability alters the structure of a portfolio. Various approaches defined sustainability using a combination of three dimensions-namely, the environmental (ecological), economic, and social dimensions [27,29]. Some criteria from the technical concerns are suggested to be integrated into the sustainability assessment [30].…”
Section: Sustainable Strategic Project Portfolio Selectionmentioning
confidence: 99%
“…They concluded that considering sustainability alters the structure of a portfolio. Various approaches defined sustainability using a combination of three dimensions-namely, the environmental (ecological), economic, and social dimensions [27,29]. Some criteria from the technical concerns are suggested to be integrated into the sustainability assessment [30].…”
Section: Sustainable Strategic Project Portfolio Selectionmentioning
confidence: 99%
“…Interaction between indicators, distinguished in static interaction and dynamic trend similarity, has been taken into account. After normalizing the evaluations of the cities by the min − max normalization, the IOWA (Induced Ordered Weighted Averaging; [63]) operator has been used to aggregate them; the IOWA operator has also been applied in [65] to analyze the sustainable development of 13 Chinese cities in the 2011-2016 period. To this aim, 18 criteria concerning economic, social, and environmental aspects have been taken into account.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Paper 4 (high-adherence class) [9] highlighted that the assessment of sustainability is an important aspect of the city.…”
Section: Municipal Budget Costs and Sustainabilitymentioning
confidence: 99%
“…In addition, effective budget distribution planning must take into account sustainable aspects that leverage economic growth, environmental protection, social responsibility, and an efficient return of investments [8]. In this way, urban sustainability advances are also an important part of social development [9].…”
Section: Introductionmentioning
confidence: 99%